Estrutura floral de espécies da tribo Cocoseae e aliados (arecaceae) - Sarah Barbosa Reis (2012)
The family Arecaceae occurs mainly in the tropics, with richest diversity in South America, where many species of the subfamily Arecoideae arepresent. Cocoseae belongs to the Arecoideae whose genera have undergone recurrent phylogenetic classification and the clade RRC (Reinhardtieae, Roystoneae, and Cocoseae) was recently proposed. This study aims assessing the structure of the flowers of Roystonea oleracea (tribe Roystoneae), Reinhardtia gracilis (tribe Reinhardtieae), and some species of Cocoseae: Acrocomia aculeata, Aiphanes horrida, Bactris gasipaes (subtribe Bactridinae), Allagoptera campestris,Butia archeri, and Syagrus glaucescens (Attaleinae tribe), looking for features that can assist in the circumscription of this group. The material was collected from the natural environment and collections of the Botanical Garden, submitted to usual methodology in plant anatomy. The species have features previously described for Arecaceae. The trimerous condition is present in all species, although R. gracilis to be polyandrous. Vasculature of the whorls was important to identify residual structures, since flowers of the RRC clade are diclinous. Vasculature also pointedstructures that are reducing; in sepals of R. oleracea and subtribe Bactridinae are unvascularized, and Attaleinae and R. gracilis has vascularized sepals. Attaleinae and R. gracilis has post-genital fusion of the carpels, and R. oleracea and Bactridinae has carpels completely fused. The vasculature of carpels and ovule is complex and variable within the clade RRC. The common features of RRC clade aredorsifixed, introrse, and dithecae anthers. Cocoseae and Reinhardtieae has trilocular ovary, with one ovule per locule; anatropous and bitegmic ovule, with phenolic inner integument. The structure of flowers of the RRC clade has taxonomic potential for distinguish subtribes